Rice bran supplementation exerts a protective effect against mitochondrial dysfunction associated with high-fat diet consumption in ovariectomized mice - Jisun Choi; Songhee Lee; Dongshin Yang; Minji Kim; Min Young Um; Sooim Shin (Applied Biological Chemistry)
Abstract Obesity results from various factors, such as menopause, age, physical activity, genetics, and environmental factors. Notably, the risk of obesity in women, especially in the context of menopause, has increased with rising life expectancy. Therefore, preventing and treating menopause-related obesity is crucial. Rice bran, the brown outer layer of the rice kernel, is known to contain nutrients and bioactive compounds. Rice bran supplement (RBS), a byproduct of rice polishing, recognizably treats obesity; moreover, it is also known to increase mitochondrial function. To validate the effect of RBS on menopause-induced obesity, we administered RBS to ovariectomized mice as a menopause model. Ultimately, we aimed to evaluate the potential of RBS as an alternative candidate to hormone replacement therapy for treating menopause-induced obesity. RBS treatment significantly reduced body weight by 20% and retroperitoneal fat by 97% compared to the HFD group. Furthermore, mitochondrial enzyme activities as mitochondrial respiratory function in the brain increased on average by 102% compared to the HFD group and by average by 93% compared to the ND group, highlighting the therapeutic efficacy of RBS in ameliorating metabolic complications associated with menopause, without the use of hormone replacement therapy.